Removal of cefdinir from aqueous solution using nanostructure adsorbents of TiO2, SiO2 and TiO2/SiO2 : equilibrium, thermodynamic and kinetic studies - Yener, Huriye Banu (Array, 2019)
The adsorptive removal of cefdinir, an antibiotic, from aqueous solutions on TiO2, SiO2 and TiO2/SiO2 nanostructures was studied by batch experiments. The SiO2 particles were obtained from rice husk ash. Investigated were the effects of the solution pH, adsorbent dosage, initial adsorbate concentration, and solution temperature on both cefdinir uptake and removal. The studies suggest that the adsorption of cefdinir on the nanostructures was mainly due to the electrostatic interaction between the ionic adsorbate molecules and charged adsorbent surface sites. The adsorption isotherm data of TiO2 and SiO2 fit well to the Langmuir isotherm model and the Freundlich model for TiO2/SiO2. The thermodynamic studies indicated favorable and spontaneous occurrence of adsorption. The kinetic data of TiO2 fitted best with PSO reaction model equation, and was described well by Weber-Morris diffusion model with dominating control mechanism of intraparticle diffusion and limited contribution of internal film diffusion.